ANALYSIS OF GROWTH AND YIELD OF SHALLOT VARIETIES WITH ORGANIC LIQUID FERTILIZER IN THE SUB-OPTIMAL LAND OF WAMENA - Tuhuteru, Sumiyati; Inrianti, Inrianti; Maulidiyah, Maulidiyah; Nurdin, Muhammad (Journal of Agriculture, 2023)
This study compares the degree of adaptation of four shallot varieties introduced to the sub-optimal land of Wamena with one local variety. The study determined the physiological processes of plants observed 5 and 11 weeks after planting. The results show that the best-adapted shallot is the local variety which is indicated by the parameter of harvest index (0.820). In addition, the results showed that the local Wamena variety produced high production with a high assimilation rate (0.072 g/dm2week-1), had a leaf area (41,750 cm) and a high leaf area value (0.465 cm) even though it was indicated by treatment without fertilizer application. Liquid organic (control treatment). Compared with the introduced varieties, which showed no significant effect on each liquid organic fertilizer treatment level. The difference in responses shown by each variety is influenced by the genetic ability of each variety which is supported by environmental conditions.